Latitudinal gradients in air density create invisible topography at sea level, affecting animal flight costs - Emily Shepard (Current Biology, 2024)
Regional patterns in wind underpin the low-cost migratory flyways of billions of birds and insects,1,2,3 but the effect of large-scale changes in temperature on flight is unknown. Flight costs should increase with rising temperatures because lift decreases as density decreases, whereas weight remains unchanged. The effects of density are well-established in the context of high-altitude movements and migration.4,5,6,7 Here, we examine the impact of air density on low-flying birds in relation to seasonal, regional, and global changes in temperature. We deployed multi-sensor loggers on red-tailed tropicbirds (Phaethon rubricauda), a large and widely distributed seabird breeding year round in Mauritius. Seasonal changes in air density caused very small differences in flight costs (1%–2%, estimated using aeronautical models) despite being the major driver of seasonal differences in wingbeat frequency. Flight costs should vary in space as well as time, and aeronautical models predicted ≥10% variation in power across the tropicbird’s range due to latitudinal temperature gradients. Changes in air density can therefore modulate flight costs across regional scales, even when birds are operating close to sea level. Indeed, creating a 20-year climatology of air density at sea level revealed that temperature gradients cause effective altitude to vary by >2 km at a global scale within a given season. This “invisible topography” at sea level could influence the biogeography of flight morphologies, particularly the distribution of birds with the highest flight costs, which generally occur in regions with relatively high air density.